Gabion styled water filtration cage / Mohd Zulkhairi Mat Salleh ... [et al.] - Mat Salleh, Mohd Zulkhairi; Haron, Hairol Anuar; Nasir, Nazri; Che Hasan, Asmawati; Muhammad Fathullah, Muhammad Farid; Mohamed Rashid, Mohamad Rohaidzat; Ab Jaba, Mohamad Faizal (2020)
For indigenous people in Bekok, Johor they rely on the waterfall as their main water supply. During the rainy season, however, the water quality deteriorated and it became unsuitable for human consumption and usage. Therefore, the most effective solution is by introducing the gabion styled water filtration cage. The filter was installed at the Takah Pengkoi waterfall water intake. The objective of the product is to reduce the turbidity of water. The cage has two layers of filtration. The first layer consists of large gravels and it helps to prevent large trashes from entering the cage. The second filter is equipped with sand and small gravels. It serves to filter smaller particles from entering the cage such as sand, silts, and other sediment loads. After testing both upstream and downstream of the filter cage, the result of the water quality index (WQI) increased by 2.75%. It indicates that the filter managed to reduce the turbidity thus improving the quality of water. This benefited almost 500 of indigenous peoples in this area where they can enjoy cleaner and higher quality of water. Subsequently, this product can be used in other rural areas that encounter a similar problem.